Analisa Faktor Yang Mempengaruhi Financial Sustainability Ratio Sektor Perbankan Di Bei Periode 2019-2022 - Pangestu, Juan Carlos; Hati, Desty Permata (Politeknik Ganesha Medan, 2024)
Financial Sustainability in banking is one of the important things to measure the bank's sustainability in the future, especially from a financial perspective. The sustainability of the banking sector must be a concern because there are many parties who will have an impact if a bank experiences failure to operate, especially in its finances. This research aims to examine the influence of BOPO, DebtToEquity, ReturnOnAsset, LDR, Directors, Commissioners on the Financial Sustainability Ratio (FSR) in Idx banking sector companies -Ic Period 2019-2022. Sampling was carried out using purposive sampling technique. This type of research uses multiple linear regression methods. The object of this research is the Idx-Ic banking sector financial report for the 2019-2022 period. The research results show that only the Director variable of the six independent variables used has an influence on the Financial Sustainability Ratio (FSR) and the research model is suitable for use. Companies that want to maintain the FSR value should pay attention to the number and selection of directors they have.